1997
DOI: 10.1002/bies.950190102
|View full text |Cite
|
Sign up to set email alerts
|

Archaebacterial genomics: The complete genome sequence of Methanococcus jannaschii

Abstract: SummaryThe first complete sequence of an archaebacterial genome, that of Methanococcus jannaschii, has recently been published('). Less than half of the open reading frames (ORFs) can be assigned a function based on similarity to known sequences in databases. These assignable ORFs fall into two general classes; those involved in transcription, translation and replication are more similar to eukaryotic homologs, while those determining metabolic processes are more similar to eubacterial versions. The immense bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the complete genome sequences of Methanococcus jannaschii and Pyrococcus horikoshii in Euryarchaeota, one DNA polymerase gene each was predicted from the similarity of the deduced amino acid sequences to family B DNA polymerases, and no more pol-like genes were found (4,16). The fact that these euryarchaeotes may survive with just a single DNA polymerase was very perplexing (8,11,19). Recently, however, a novel two-subunit DNA polymerase whose sequence has no similarity to that of any DNA polymerase family was identified in Pyrococcus furiosus (28), in addition to a family B DNA polymerase isolated earlier from this organism (30).…”
mentioning
confidence: 99%
“…In the complete genome sequences of Methanococcus jannaschii and Pyrococcus horikoshii in Euryarchaeota, one DNA polymerase gene each was predicted from the similarity of the deduced amino acid sequences to family B DNA polymerases, and no more pol-like genes were found (4,16). The fact that these euryarchaeotes may survive with just a single DNA polymerase was very perplexing (8,11,19). Recently, however, a novel two-subunit DNA polymerase whose sequence has no similarity to that of any DNA polymerase family was identified in Pyrococcus furiosus (28), in addition to a family B DNA polymerase isolated earlier from this organism (30).…”
mentioning
confidence: 99%
“…Surprisingly, it was found that this genome includes only one open reading frame with a sequence homologous to ␣-like DNA polymerases and lacks other DNA polymerase sequences. One of the most controversial issues from the first complete genome sequence from Archaea is whether this organism indeed possesses only one DNA polymerase (3,4,6,11). More definitely, it would be very surprising if the life of this archaeon were dominated by only a single DNA polymerase with a unique mechanism, since it is well established that both eucaryotic and eubacterial cells contain several DNA polymerases involved in replication and repair.…”
mentioning
confidence: 99%
“…However, our knowledge on the DNA polymerases and DNA replication in Archaea at that time was so fragmentary. The complete genome sequence of the hyperthermophilic euryarchaeote, Methanococcus jannaschii (Bult et al, 1996), complicated the issue by suggesting that this organism depends on a single DNA polymerase for its DNA metabolic functions (Edgell and Doolittle, 1996;Gray, 1996;Morell, 1996). Three complete genome reports of other members of this subdomain (Kawarabayasi et al, 1998;Klenk et al, 1997;Smith et al, 1997) seem to substantiate this puzzling observation.…”
Section: Introductionmentioning
confidence: 99%